FAST DISSOLVING DRUG DELIVERY SYSTEMS: FORMULATION, PREPARATION TECHNIQUES AND EVALUATION - Singh, Satbir; Virmani, Tarun; Virmani, Reshu; Mahlawat, Geeta; Kumar, Pankaj (Universal Journal of Pharmaceutical Research, 2018)
The Fast Dissolving Drug Delivery Systems sets a new benchmark was an expansion that came into existence in the early 1980’s and combat over the use of the different dosage form like tablets, suspension, syrups, capsules which are the other oral drug delivery systems. Fast Dissolving Drug Delivery System (FDTS) has a major advantage over the conventional dosage forms since the drug gets rapidly disintegrated and dissolves in the saliva without the use of water .In spite of the downside lack of immediate onset of action; these oral dosage forms have valuable purposes such as self medication, increased patient compliance, ease of manufacturing and lack of pain. Hence Fast Disintegrating Tablets (FDTS) technology has been gaining importance now-a-days with wide variety of drugs serving many purposes. Fast Disintegrating Tablets (FDTS) has ever increased their demand in the last decade since they disintegrate in saliva in less than a minute that improved compliance in pediatrics and geriatric patients, who have difficulty in swallowing tablets or liquids. As fast dissolving tablet provide instantaneous disintegration after putting it on tongue, thereby rapid drug absorption and instantaneous bioavailability, whereas Fast dissolving oral films are used as practical alternative to FDTS. These films have a potential to deliver the drug systemically through intragastric, sublingual or buccal route of administration and also has been used for local action. In present review article different aspects of fast dissolving tablets and films like method of preparations, latest technologies, evaluation parameters are discussed. This study will be useful for the researchers for their lab work. Peer Review History: Received 26 May 2018; Revised 5 July; Accepted 12 September; Available online 15 September 2018 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Omnia Momtaz Al-Fakharany , Tanta, University, Eygpt, amina.elfakharany@pharm.tanta.edu.eg Essam Mohamed Eissa , Beni-Suef – 32 Tahrir St, Egypt, dressamceutics@yahoo.com